Novel combined desalination, heating and power system: Energy, exergy, economic and environmental assessments - Saini P.; Singh J.; Sarkar J. (My University, 2025)
Current research proposes and investigates a novel small-scale solar-driven sustainable combined desalination, heating and power (CDHP) system for a house in cold remote locations and hill stations. Latent heat storage integrated evacuated tube solar collector, organic Rankine's cycle, active solar still and water heater are main subsystems of the proposed system to generate power, potable water and hot water simultaneously. Therminol-66 and eco-friendly organic substance (n-butane) are selected as working fluids for the collector system and organic Rankine's cycle, respectively. Heating oil flow is divided after vapor generator to get best temperature glide and hence exergetic performance. The system is assessed based on multi-objective functions like power output, heating output, water productivity, component irreversibility, subsystems and overall system energy and exergy efficiencies, economic and environmental criterion. Generator temperature, condenser temperature, preheater mass fraction and pinch point temperature difference cases are selected decision variables for the parametric studies. The CDHP system energy efficiency, exergy efficiency, cost rate and CO2 reduction are obtained as 17.89%, 3.915%, 1784 $/yr and 10.806 tonnes, respectively, at mean operating conditions. Furthermore, the maximum exergy efficiency of organic Rankine's cycle is found as 57.46% at optimum generator temperature of 119 °C for 50% preheater mass fraction. Overall, the current CDHP system is recommended to produce power, potable water and hot water to meet energy demands, especially at cold remote locations. © 2021 Elsevier Ltd